(untitled) (Journal of the College of Education for Women, 2019)
In this research, we attempt to show the extent of harmony in an aspect of the text according to the stylistics for the Knowing of the stylistic value of the title threshold, and the pathways of titles that suggest and support the meaning when the recipient reads the literary text, in addition to the interpretations that reflect the purposes of the poet who contributed to the drawing of his poetic achievement. The research presented a brief about the poet and his most important works, because they are the text which will be studied according to the stylistics. The research also explained the concept of style and the stylistics in the preface , because of the stylistic is the method adopted by the research to study the title thresholds in ,Muhammad’s Ali Kazem Haider poetry, and then the research talked about the stylistic structure of the titles of poems and tried to study the relations that connect between the thresholds of poems and their contents . in the last, the research concluded the most important results of this study.